2002
DOI: 10.1103/physreve.66.016407
|View full text |Cite
|
Sign up to set email alerts
|

Krook collisional models of the kinetic susceptibility of plasmas

Abstract: An assessment is made of Krook collisional models used to describe the kinetic behavior of collective oscillations, i.e., when Landau damping and collisions must be considered, as is often the case for low-frequency waves. The study focuses on an early energy-conserving model [B. D. Fried, A. N. Kaufman, and D. L. Sachs, Phys. Fluids 9, 292 (1966)] that is shown to be identical to a more modern version used in drift-wave stability studies [G. Rewoldt, W. M. Tang, and R. J. Hastie, Phys. Fluids 29, 2893 (1986)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 20 publications
2
45
0
1
Order By: Relevance
“…To obtain qualitative descriptions of collisional regimes of a plasma the Bhatnagar-Gross-Krook (BGK) [18] collisional model in the kinetic equation for electrons has been widely used with or without number-conservation procedure [7,[19][20][21][22][23][24]. The appeal of this model is its simplicity, which in its original nonconserving form amounts to the replacement of ω → ω+iν in the argument of the plasma dispersion function, where ν is a model collision frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain qualitative descriptions of collisional regimes of a plasma the Bhatnagar-Gross-Krook (BGK) [18] collisional model in the kinetic equation for electrons has been widely used with or without number-conservation procedure [7,[19][20][21][22][23][24]. The appeal of this model is its simplicity, which in its original nonconserving form amounts to the replacement of ω → ω+iν in the argument of the plasma dispersion function, where ν is a model collision frequency.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] and [27,28], respectively, which yield analytic expressions for the permittivities in terms of combinations of the plasma dispersion function. However, for a completely ionized plasma, the model permittivity within the BGK approximation and the corresponding Drude model for the transverse permittivity [7,[22][23][24] lead to the significant deviations from the known limiting cases in the range of moderate and strong collisions [29][30][31]. For instance, it has been found that this model cannot reproduce the plasma permittivity in the strongly collisional hydrodynamic regime considered in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently completed an assessment of Krook collisional models. We found that not only the energy and number conserving operators but also the number conserving Krook operator are adequate to capture collisional effects in the kinetic regime compared to the Lorentz and Lenard-Bernstein collision operators which are more complicated to implement and calculate [LD11]. This effort will help greatly in guiding inclusion of collisions in our particle models.…”
Section: ) Other Accomplishmentsmentioning
confidence: 95%
“…Конкретно, мы рассмотрим представление интеграла столкновений в форме стандарного модельного БГК-интеграла столкновений [11] (см. также работу [27], где проведено исследование этой модели). Тогда предыду-щее уравнение перепишется в виде…”
Section: решение кинетического уравненияunclassified